National security of Russia and world politics - Petrovchuk A. Y., Poslova A. S. (Interactive science, 2017)
in the article the value of criteria of national security in culture of society is investigated. The authors describe the structural maintenance of world politics in modern culture of scientific knowledge.
Keywords: культура; национальная безопасность; culture; national security; философия политики; policy philosophy; мировая политика; world politics